2008
DOI: 10.1007/s10461-008-9398-9
|View full text |Cite
|
Sign up to set email alerts
|

Late Presentation to Care for HIV Infection in Croatia and the Effect of Interventions During the Croatian Global Fund Project

Abstract: There are limited data on how HIV prevention interventions affect individuals presenting to care in settings with a low-level HIV epidemic. We examined whether interventions undertaken during the Croatian Global Fund Project in 2004-2006 had an influence on patients entering care. The number of men who have sex with men (MSM) presenting in 2004-2006 (n = 86) was 59% higher than in 2001-2003 (n = 54); in heterosexual patients the increase was 14% (n = 51 in 2001-2003; n = 58 in 2004-2006). MSM presented at a yo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 15 publications
2
10
0
Order By: Relevance
“…United Kingdom researchers observed a higher percentage (48%) of late presenters among people aged 50 years and over compared with 33% among younger individuals [22]. Reports from Croatia and Denmark concur with our observation that a significantly higher proportion of heterosexual patients than homosexuals are late presenters [23,24].…”
Section: Discussionsupporting
confidence: 88%
“…United Kingdom researchers observed a higher percentage (48%) of late presenters among people aged 50 years and over compared with 33% among younger individuals [22]. Reports from Croatia and Denmark concur with our observation that a significantly higher proportion of heterosexual patients than homosexuals are late presenters [23,24].…”
Section: Discussionsupporting
confidence: 88%
“…Individuals diagnosed early may be less likely to transmit the virus to others, not only because treatment has reduced their infectivity but also because they have modified their risk behaviors [27]. In a study in Croatia, Begovac et al showed that HIV-infected heterosexuals seek medical treatment at a later stage of infection than do MSM because heterosexuals test for HIV less often than MSM [28]. This may be because heterosexuals perceive themselves to be at lower risk of infection.…”
Section: Discussionmentioning
confidence: 99%
“…This policy may be ineffective in the case of individuals who fail to self-identify risk behaviors or who nevertheless perceive themselves to be at lower risk of acquiring HIV. Such individuals may be more likely to be unaware HIV carriers who transmit infection and present late to treatment, resulting in a worse prognosis [28].…”
Section: Discussionmentioning
confidence: 99%
“…9(10), (2011) frequencies of late presentation of 10-55% where a threshold of <50 cells/mm 3 is used [16,[20][21][22], 23-85% where a threshold of <200 cells/mm 3 is used [5][6][7]9,13,16,21,23] and 54-63% where a threshold of <350 cells/mm 3 is used [24][25][26]. Additional inclusion of those with an AIDS-defining event results in a further increase in the apparent frequency of late presenters to 29-59% [9,10, 19,21,27,28]. Definitions based on clinical events or hospitalizations alone (without any restriction on the CD4 count) result in reported frequencies of 13-42% [5,8,13,18].…”
Section: What Do We Mean By a 'Late Presenter'?mentioning
confidence: 99%
“…The required time interval between a positive HIV test result and a low CD4 count or clinical event may also vary; for example, while some studies only include as late presenters those who have a low CD4 count or clinical event at the time of a first positive HIV test [5,13,15,16], others include any individuals meeting the criteria within the first 3 months [5,10] or year [9,17,18] after HIV diagnosis. As HIV seroconversion itself is associated with a temporary drop in CD4 counts, often to low levels, some studies actively exclude individuals diagnosed during this high-risk period [19].…”
mentioning
confidence: 99%